A microfluidic fully paper-based analytical device integrated with loop-mediated isothermal amplification and nano-biosensors for rapid, sensitive, and specific quantitative detection of infectious diseases. Issue 23 (9th November 2022) - Tavakoli, Hamed; Hirth, Elisabeth; Luo, Man; Sharma Timilsina, Sanjay; Dou, Maowei; Dominguez, Delfina C.; Li, XiuJun
Abstract : A microfluidic fully paper-based analytical device integrated with loop-mediated isothermal amplification (LAMP) and graphene oxide nanosensors was developed for the first time for rapid, low-cost, and quantitative detection of infectious diseases. Abstract : Bacterial meningitis, an infection of the membranes (meninges) and cerebrospinal fluid (CSF) surrounding the brain and spinal cord, is one of the major causes of death and disability worldwide. Higher case-fatality rates and short survival times have been reported in developing countries. Hence, a quick, straightforward, and low-cost approach is in great demand for the diagnosis of meningitis. In this research, a microfluidic fully paper-based analytical device (μFPAD) integrated with loop-mediated isothermal amplification (LAMP) and ssDNA-functionalized graphene oxide (GO) nano-biosensors was developed for the first time for a simple, rapid, low-cost, and quantitative detection of the main meningitis-causing bacteria, Neisseria meningitidis ( N. meningitidis ). The results can be successfully read within 1 hour with the limit of detection (LOD) of 6 DNA copies per detection zone. This paper device also offers versatile functions by providing a qualitative diagnostic analysis ( i.e., a yes or no answer), confirmatory testing, and quantitative analysis. These features make the presented μFPAD capable of a simple, highly sensitive, and specific diagnosis of N. meningitis . Furthermore, this microfluidic approach has great potential in the rapid detection of a wide variety of different other pathogens in low-resource settings.